Can Dynamic Changes in Inflammatory Markers Predict Outcomes in COVID-19 Infection? - Tahir, Umama; Muhammad, Siraj; Arshad, Abdul Rehman; Mallhi, Muhammad Azam; Tahir, Yumna (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the role of dynamic changes in inflammatory markers over initial 48 hours after admission in predicting outcomes of COVID-19 infection. Study Design: Cross-sectional study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Peshawar Pakistan, from Sep to Dec 2020. Methodology: Indoor patients with positive polymerase chain reaction test for SARS-CoV-2 were included in the study. Serum C-reactive protein, Ferritin and LDH levels were tested within 60 minutes of admission and the course of these markers was monitored over 48 hrs. In-hospital mortality was also recorded. Results: There were 92 patients in this study, having a mean age of 53.80±16.20 years. In-hospital, 14 patients (15.22%) died whereas the rest were discharged. Median and interquartile ranges for changes in Serum CRP, Ferritin and LDH over the first 48 hours of admission were -10.00(-56.35–2.68) mg/L, -5.50(-100.00–193.50) ng/ml and -23.50(-162.00–81.50) U/L respectively. Increase in Serum Ferritin ≥128.5 ng/ml had 64.29% sensitivity and 74.36% specificity for predicting in- hospital mortality. Changes in C-reactive protein and Lactate Dehydrogenase did not have a predictive role in our study. Conclusion: Rise in Serum Ferritin levels over first two days of admission was associated with increased risk of death.